228k views
3 votes
Question 6: Difference Quotient​

Question 6: Difference Quotient​-example-1
User Kufi
by
4.5k points

1 Answer

3 votes

Answer:

see explanation

Explanation:

(a)

f(x) = 2x + 5 , then difference quotient is


(2(x+h)+5-(2x+5))/(h)

=
(2x+2h+5-2x-5)/(h)

=
(2h)/(h)

= 2

(b)

f(x) = 3x² + x , then difference quotient is


(3(x+h)^2+(x+h)-(3x^2+x))/(h)

=
(3(x^2+2hx+h^2+x+h-3x^2-x)/(h)

=
(3x^2+6hx+3h^2+x+h-3x^2-x)/(h)

=
(6hx+3h^2+h)/(h)

=
(h(6x+3h+1))/(h)

= 6x+3h+1

User Srbrills
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.